2022
DOI: 10.3889/oamjms.2022.7433
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Surgical Advancement Outcomes of Retruded Maxilla in a Group of Egyptian Cleft Lip and Palate Subjects

Abstract: BACKGROUND: Cleft lip and palate (CLP) is one of the most common congenital deformities involving intervention in several sub-specialties. AIM: The present study was conducted to investigate the amount of maxillary advancement obtained by three different methods. METHODS: A retrospective comparative study was conducted on 24 CLP patients who were treated with three surgical maxillary advancement techniques: Group A was treated with Le Fort I (LFI) orthognathic surgery with bone grafting and rigid fixation (LFI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Patients with cleft lip and palate who may have a retruded maxilla may have psychological and functional issues as a result of their appearance. [ 24 ] The participants in this study were 20 pubertal patients who underwent non-surgical maxillary advancement using an orthopaedic face mask with elastic traction. The results of this study demonstrated that when the face mask approach was used, both upper and lower lip soft-tissue points improved significantly, while nasal soft-tissue points remained unaltered, necessitating more management in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cleft lip and palate who may have a retruded maxilla may have psychological and functional issues as a result of their appearance. [ 24 ] The participants in this study were 20 pubertal patients who underwent non-surgical maxillary advancement using an orthopaedic face mask with elastic traction. The results of this study demonstrated that when the face mask approach was used, both upper and lower lip soft-tissue points improved significantly, while nasal soft-tissue points remained unaltered, necessitating more management in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial proportion of patients suffer from posterior cross-bite associated with significant maxillary deficiency, high arched palate, and airway constriction. This could present in mild to severe forms according to the associated skeletal growth abnormalities, or congenital clefts [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Absence of volume is mainly caused by soft tissue deficiency, insufficient planning and inability to reconstruct the lower part of the Orbicularis Oris muscle during the initial lip repair. [6][7][8] If more bulk is needed, relatively small filler grafts can be used. Subcutaneous tissue flaps and autologous fascial, fat graft or dermal fillers are also used.…”
Section: Introductionmentioning
confidence: 99%